PERAN BIDAN TERHADAP PELAKSANAAN PROGRAM PERENCANAAN PERSALINAN DAN PENCEGAHAN KOMPLIKASI (P4K) DALAM MENURUNKAN ANGKA KEMATIAN IBU - Siskha Maya Herlina; Yesvi Zulviana; Yadul Ulya (J-KESMAS: Jurnal Kesehatan Masyarakat, 2021)
Maternal Mortality Rate in Indonesia in 2012 that there were 359. In 2007 the Minister of Health planned a delivery planning and complication prevention program (P4K) as an effort to accelerate the decline in MMR in Indonesia. Health workers have a role in carrying out labor preparation and preparation for pregnant women. This program is one of the effective strategies to reduce the number of maternal deaths, besides childbirth assisted by trained midwives also plays a role in reducing maternal morbidity and mortality. Program Implementation Planning Childbirth Complications and Prevention (P4K) on Reducing Maternal Mortality Rate (MMR) Methods phenomenological design, using descriptive data involving  informants. The collection of data with verification, data presentation and verification. Results In this study Generally P4K implementation is good enough. Services and cooperation of midwives, as well as the role of all the informant was quite good, facilities are adequate, but there are some activities that still has not been implemented because some of the barriers that exist so that the implementation is not optimal. Conclusions Implementation P4K program is likely to have contributed in helping pregnant women prepare for childbirth, and to reduce maternal mortality (MMR) should be reconsidered from various aspects